Pengembangan (Insinerator) Teknologi Pembakaran Sampah Rendah Emisi dengan Sistem Rocket Stove - Diana Romdhoningsih; Ilham Jagat Prediksa; Muhammad Reno Widodo; Wahid Falhuddin; Aida Alfita (Lembaga Pengembangan Kinerja Dosen, 2025)
This Community Service activity aims to evaluate and implement low-smoke waste incinerator technology based on the rocket stove method as a solution to environmental pollution due to inefficient waste burning. This technology allows the waste burning process to be carried out at high temperatures efficiently, resulting in lower smoke emissions and is environmentally friendly. The main focus of the activity is to assist the residents of Bojong Loa Village in increasing waste management capacity through an educational and participatory approach. The methods used include environmental education, technical training, operational assistance, and the transfer of incineration technology to the community. The program is designed to produce a tool that is practical, energy-efficient, and easy to operate by citizens, with the hope that it can be widely adopted in rural environments. The implementation of activities was carried out intensively over a certain period, involving a team of academics and local partners as facilitators. The results of the activity show that the minimal-smoke incinerator has been successfully modified and available for public use. There has been a significant increase in the knowledge and skills of the residents of Bojong Loa Village in operating the equipment, which is shown through technical capabilities and an understanding of the principle of clean combustion. Another positive impact is the creation of a more effective waste management system, contributing to reducing air pollution levels and improving people's quality of life. This initiative proves that community service has a strategic role in introducing innovative and sustainable waste management technology. The success of this program opens up opportunities for replication in other regions, as well as encouraging collaboration between academics, government, and society in realizing a cleaner and healthier environment.